2003
DOI: 10.1096/fj.02-0824fje
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular expression of endostatin reduces VEGF‐induced retinal vascular permeability, neovascularization, and retinal detachment

Abstract: Endostatin, a proteolytic fragment of collagen XVIII, is an endogenous inhibitor of tumor angiogenesis that also inhibits choroidal neovascularization. In this study, we assessed the effects of increased intraocular expression of endostatin on vascular endothelial growth factor (VEGF)-induced changes in the retina. After subretinal injection of a pair of gutless adenoviral vectors (AGV) designed to provide tamoxifen-inducible expression of endostatin, diffuse endostatin immunoreactivity was induced thoroughout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 119 publications
(81 citation statements)
references
References 47 publications
3
78
0
Order By: Relevance
“…Indeed, an in vivo study by Takahashi et al (2003) showed intraocular expression of endostatin suppressed leakage of intravascular [ 3 H] mannitol into the retina. However, it was not possible to determine concentrations of endostatin that have an effect using this experimental approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, an in vivo study by Takahashi et al (2003) showed intraocular expression of endostatin suppressed leakage of intravascular [ 3 H] mannitol into the retina. However, it was not possible to determine concentrations of endostatin that have an effect using this experimental approach.…”
Section: Discussionmentioning
confidence: 99%
“…This peptide can prevent tumour angiogenesis (O'Reilly et al, 1997) and has also been shown to be efficacious in the eye by preventing retinal and choroidal neovascularisation (Mori et al, 2001, Auricchio et al, 2002and Le Gat et al, 2003. Endostatin may also prevent vasopermeability responses by growth factors and recent studies have suggested that endostatin can reduce VEGF-induced retinal vascular permeability in double transgenic mice with inducible expression of VEGF 165 in the retina (Takahashi et al, 2003). VEGF-induced permeability was assessed via [ 3 H] mannitol permeation, fluorescein angiography and assessment of edema was conducted by measurement of retinal thickness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The doxycycline inducible promoter system in transgenic mice is a very useful tool, which in past studies has allowed detailed exploration of the effects of VEGF 19,20 and brain-derived neurotrophic factor in the retina. 21 It requires generation of two transgenic mice, one in which reverse tetracycline transactivator is coupled to a promoter that drives its expression ubiquitously or in a certain tissue.…”
Section: Double Transgenic Mice With Inducible Expression Of Ang1 In mentioning
confidence: 99%
“…Expression of pigment epithelium-derived factor (PEDF) has been shown to suppress ocular neovascularization in several models (Mori et al, 2001a(Mori et al, ,b, 2002Auricchio et al, 2002;Raisler et al, 2002;Gehlbach et al, 2003a) and a phase I trial in patients with neovascular AMD showed promise . Other promising transgenes for treatment of ocular neovascularization include endostatin, which reduces excessive vascular permeability in addition to suppressing neovascularization (Auricchio et al, 2002;Takahashi et al, 2003), angiostatin (Lai et al, 2001a;Raisler et al, 2002;Igarashi et al, 2003), and soluble VEGF receptor 1 (Honda et al, 2000;Lai et al, 2001bLai et al, , 2005Bainbridge et al, 2002;Gehlbach et al, 2003b;Rota et al, 2004).…”
Section: Ocular Gene Therapymentioning
confidence: 99%